Implementation of Value Stream Mapping to Increase PT RCI's Productivity and Efficiency - Setiawan Dwima Saputro; Salma Faizah; Novi Afriyani Ramdani; Dade Andika; Rinaldi Aditya Gunawan (Universitas KH. Abdul Chalim Mojokerto, 2024)
Competition in the logistics business requires companies to develop and increase production efficiency and effectiveness. One of the companies operating in the logistics sector is PT. RCI found many problems during the warehousing service process. This hampers other processes. The problem faced by companies is not achieving production targets because there are still many non-value-added activities that are classified as waste. The research aims to eliminate waste that occurs in the Quality Control process, or checking goods at PT. RCI with a lean manufacturing approach. The lean manufacturing method used is value stream mapping (VSM) to analyze the dominant waste in the manufacturing process. Based on the results of the analysis, three recommendations for improvement were obtained, namely the use of forklifts, additional work tools, and additional changes to the layout of the goods checking location. Recommendations from the results obtained an increase in the Process Cycle Efficiency value of 29.50%.